2003
DOI: 10.1002/jnr.10852
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation improves open field locomotor recovery after low but not high thoracic spinal cord compression‐injury in adult rats

Abstract: Electromagnetic fields are able to promote axonal regeneration in vitro and in vivo. Repetitive transcranial magnetic stimulation (rTMS) is used routinely in neuropsychiatric conditions and as an atraumatic method to activate descending motor pathways. After spinal cord injury, these pathways are disconnected from the spinal locomotor generator, resulting in most of the functional deficit. We have applied daily 10 Hz rTMS for 8 weeks immediately after an incomplete high (T4-5; n = 5) or low (T10-11; n = 6) tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 66 publications
1
16
0
2
Order By: Relevance
“…An MF can noninvasively create electric fields in deep underlying structures, thereby modulating oxidative stress, apoptosis, release of neurotransmitters, secretion of neurotrophic factors, and axonal growth. [26][27][28][29][30][31] In rat models of spinal cord injury (SCI), exposure to a low intensity MF results in significant improvement in locomotor, sensorimotor, and autonomic function. [32][33][34][35][36] Stimulation of the motor cortex by repetitive transcranial magnetic stimulation is beneficial, especially in lower thoracic SCI lesions, because it activates the central pattern generator via descending serotonin pathways.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An MF can noninvasively create electric fields in deep underlying structures, thereby modulating oxidative stress, apoptosis, release of neurotransmitters, secretion of neurotrophic factors, and axonal growth. [26][27][28][29][30][31] In rat models of spinal cord injury (SCI), exposure to a low intensity MF results in significant improvement in locomotor, sensorimotor, and autonomic function. [32][33][34][35][36] Stimulation of the motor cortex by repetitive transcranial magnetic stimulation is beneficial, especially in lower thoracic SCI lesions, because it activates the central pattern generator via descending serotonin pathways.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36] Stimulation of the motor cortex by repetitive transcranial magnetic stimulation is beneficial, especially in lower thoracic SCI lesions, because it activates the central pattern generator via descending serotonin pathways. 28 In vitro, exposure to an MF increases the overall viability of mouse monoclonal hippocampal HT22 cells and has a neuroprotective effect against oxidative stressors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several recently published reviews and books describing application of rTMS in several disorders of the central nervous system (CNS) (Pascual-Leone, et al, 2002;Walsh and Pascual-Leone, 2003), although reports describing the application of this type of stimulation directly to the site of the spinal cord/nerve injury are rare (Wilson and Jagadeesh, 1976;Orgel et al, 1984). Cranial application of rTMS was reported to significantly improve locomotor recovery after spinal cord lesions in rats (Poirrier et al, 2004) and humans (Belci et al, 2004). The mechanism by which rehabilitation and physical therapy improves function, after SCI, is still not well understood (Thuret et al, 2006), and there are no reports about the influence of skilled motor training, combined with MS, on functional recovery after SCI.…”
mentioning
confidence: 99%
“…The procedure has been proven to be beneficial in brain [Vorel and Lisanby, 2008;Loo, 2008], and spinal cord pathologies [Wilson and Jagadeesh, 1976;Belci et al, 2004;Poirrier et al, 2004;Ahmed and Wieraszko, 2008]. It has been suggested that this improvement might occur due to rTMS-induced enhancement of cortical neuronal plasticity [Rossi and Rossini, 2004].…”
Section: Introductionmentioning
confidence: 98%